Resepsi Penonton Terhadap Makna Stereotip Gender Perempuan dalam Film Barbie Karya Greta Gerwig - Rida Satriani; Nuraida Nuraida; Emi Puspita Dewi (ScidacPlus, 2024)
Greta Gerwig's Barbie is one of the films that highlights women's gender issues, features various scenes with certain stereotypes, and gets a variety of responses from the audience. This phenomenon is interesting to study about how the audience's reception analysis of the meaning of female gender stereotypes in Greta Gerwig's Barbie Movie. Based on these problems, this study aims to determine the audience's interpretation process of gender messages contained in the film. This research method uses Stuart Hall's reception analysis with data collection through interviews, documentation, and literature study. The informants in the study amounted to 5 Barbie movie viewers who were selected based on purposive sampling technique. The results of this study show that there are variations in the interpretation of 4 indicators of female gender stereotyping messages in Barbie Movies with different position categories, namely dominant, negotiation, and opposition positions. There are certain parts of the informants agreeing to the message of female gender stereotypes displayed in the Barbie Movie, but there are parts when the informants are still negotiating the message, and there are informants who do not agree with the movie message in certain parts influenced by a number of factors Some of the influencing factors are educational factors, environmental factors, and cultural factors which are the basis for interpreting gender stereotypical messages carried out by informants.